Australia: Entrenched Phobias, Illusory Protections - Michel Pérez (L'Espace Politique)
For millions of young Europeans, Australia is a land of dreams, with her vast and varied spaces, the red soil of her deserts and her thousands of kilometres of idyllic beaches. It is also a country of freedom with a huge economic potential, not to mention her relaxed and casual lifestyle that is perhaps her greatest asset.Yet it is also a restless country, as amply demonstrated by her history, past and recent, a nation filled with contradictions that only reinforce her ancestral fears and lead her to reject any form of difference. This study will address these concerns.